Visual effect of air pollution on the need for arousal and variety-seeking behavior - Zhang, Han; Huang, Guanling; Lin, Ping; Chen, Xiuqi; Lin, Wenhe (Frontiers in Psychology, 2024)
Research on air pollution, a commonly encountered environmental factor, has focused on physical health, mental health and cognitive health. However, air pollution-induced achromatic color, one of the most prominent features of air pollution, has received little attention. This article explored how air pollution influences variety-seeking purchase behavior through two scenario-based experiments and primed manipulation (Study 1 & Study 2) and one natural experiment using data from a local fruit chain store (Study 3). Study 1 tested the main effect of air pollution on variety-seeking and found that primed air pollution increased variety-seeking when consumers purchased beverages. Study 2 broadened the category and tested the mechanism, and the results indicated that primed air pollution increased the variety of purchased chocolates and demonstrated the mediating effect of the need for arousal. Study 3 tested the boundary condition and extended the external validity with actual purchases, which revealed that severe air pollution boosted purchased SKUs by 22.9% and visibility weakened the moderation effect.This research extended the literature on the visual effect of air pollution by providing evidence of the impact of air pollution on variety-seeking through the need for arousal, and the results implied that managers could increase sales by offering more varied goods on days with air pollution.